DUNES, THREATS, AND ALTERNATIVES FOR THEIR CONSERVATION IN LA PAZ, MEXICO - Cariño Olvera, Martha Micheline (2025)
Coasts and river banks have historically been locations for human settlements due to the convenience of access to food and communication. However, entering the 21st century, the global expansion of a tourism and residential model centered on an imaginary that links social status with housing by the sea and/or direct access to its landscape has exacerbated this trend, as well as affected the coastlines ecosystem services. Despite growing research and regulation for marine and coastal management and conservation, dune ecosystem deterioration prevails. One reason for this is the lack of studies from the social sciences that clarify the complexity of socioecological reality. Using a participatory action research approach, this article analyzes the characteristics, threats and conflicts faced by the dunes of La Paz bay (Baja California Sur, Mexico). The results reflect: changes in ways of life in the socio-ecosystem, from fishing ranch to residential and tourist use; negative impact on dune ecosystems from construction and recreational vehicles traffic due to real estate and tourism pressure; and absence of effective regulation that guarantees its conservation. To avoid still reversible collapse, management and conservation strategies involving multi-stakeholder participation are proposed to safeguard the ecosystem services provided by dunes in coastal areas.